The satirical illustrations intended to Islam found in Charlie Hebdo magazine's cartoons in the news: a pierce's semiotic analysis - Rizka Ananda (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2020)
wt,1/adil,c.1